Morphometric Analysis of Permanent Canines: Preliminary Findings on Odontometric Sex Dimorphism - Alanazi, Abdulelah A.; Almutair, Abdulmohsen Musaad; Alhubayshi, Abdullah; Almalki, Abdullah; Naqvi, Zuber Ahamed; Alassaf, Abdullah; Almulhim, Basim; Alghamdi, Sara Ayid; Mallineni, Sreekanth Kumar (International journal of environmental research and public health, 2022)
Aim: This study aims to investigate the morphometrics of permanent canines in establishing sexual dimorphism in the native Arabian population. Methods: Thirty (male = 12; female = 18) native Arabian subjects, with ages ranging between 20–45 years. The mesiodistal (MD), cericoincisal (CI) and labiolingual (LL) widths of the teeth 13, 23, 33, and 43 and the inter-canine distance in maxillary (MaxICW) and mandibular (ManICW) arches were measured using a digital caliper. The gran method was used for establishing sex dimorphism among the study subjects. Descriptive statistics were employed using SPSS version 20.0 (Armonk, NY, USA, IBM Corp.). Results: The comparison of either of the measurements (MD, CI, LL, MaxICW and ManICW) were shown to be statistically significant (p > 0.05). The overall mean values of teeth 13, 23, 33, and 43 for CI, LL, MaxICW, and ManICW were lower for females than males (p > 0.05). The MD width was higher in females than that of males (p > 0.05). The sex dimorphism value for teeth 13, 23, 33, and 43 were 0.98, 0.99, 1, and 0.99, respectively. The standard canine index was high for mandibular teeth and lower for mandibular teeth, and SCI values for teeth 13, 23, 33, and 43 were 0.219, 0.218, 0.257 and 0.256, respectively. Conclusion: The morphometrics of permanent canines are helpful in sex determination with the aid of odontometric analysis.